Burning alters the decomposition of residual plant litters in Calamagrostis angustifolia wetlands in the Sanjiang Plain (Northeast China) - Gao, Chuanyu; Wang, Guoping; Cong, Jinxin; Han, Dongxue; Zhao, Hongmei (Frontiers in Ecology and Evolution, 2022)
Wetlands store > 30% of the global soil carbon pool, which is important for global carbon cycling. However, with global warming and the increase in regional human activities, an increasing number of wetlands are being threatened by fires, which have serious effects on carbon cycling in wetlands. Although plant litter decomposition is one of the key stages of carbon cycling in wetlands, it is still unclear whether fires affect residual plant litter decomposition in burnt wetlands and whether the fire season also causes different effects. To address these knowledge gaps, a plant litter decomposition experiment was conducted during the growing season in autumn burnt, spring burnt, and unburnt sites in a Calamagrostis angustifolia marsh wetland in the Sanjiang Plain (Northeast China). The results show that autumn burning promotes more carbon loss and accelerates the decomposition of plant litter, whereas spring burning decreases the decomposition rates of plant litter. As the decomposition time increased, the accumulation index indicated that carbon was released from plant litter to the surrounding environment accompanied by mass loss and nutrient elements accumulated in the residual plant litter. The N/P ratio of plant litter decreased from ca. 20 on day 26th to ca. 9 on day 121st, indicating that N acts as the limiting element for plant litter decomposition in C. angustifolia marsh wetlands, and the limitation increased with increasing decomposition time.